A Multidimensional Version of Levin's Secular Constant Theorem and its Applications - Favorov, S.Yu.; Girya, N. (Фізико-технічний інститут низьких температур ім. Б.І. Вєркіна НАН України, 2007)
We study holomorphic almost periodic functions on a tube domain with the spectrum in a cone. We extend to this case Levin's theorem on a connection between the Jessen function, secular constant, and the Phragmen-Lindeloof indicator. Then we obtain a multidimensional version of Picard's theorem on exceptional values for our class.